Literacy: current challenges and new approaches - Prioste, Claudia [UNESP]; Carvalho Mazzeu, Francisco Jose [UNESP]; Barbosa, Eliza Maria [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
The purpose of this text is to present the special issue of the Ibero American Journal of Education Studies that focuses the Literacy as a theme, addressed under a multiplicity of aspects, dimensions and theoretical-methodological approaches. By grouping the articles according to their object, we try to indicate links between it which stimulate authors' debate and the identification of convergences and divergences, inviting to a deepening themes and to search for overcoming the mentioned challenges. The richness of approaches and analyzes represented by authors from diverse theoretical lines and institutional affiliation from all regions of Brazil and abroad brings an instigating panorama that could serve as reference for future research and actions in the field of Literacy.
Keywords: Literacy; Public policies; School failure; Literacy training; Literacy methods